Endopedon pada Tanah yang Berkembang dari Batuan Ultrabasa di Desa Kiram Kecamatan Karang Intan Kabupaten Banjar - Muhammad Abiyyu Zakly; Syaifuddin Syaifuddin; Abdul Haris (Acta Solum, 2024)
Endopedon identification is very necessary to determine the development, physical and chemical properties of soil. The development of endopedons originating from ultramafic rocks around Kiram Village, Karang Intan District, Banjar Regency has not been studied much, therefore it is necessary to explore more about the results of soil development. This research was a descriptive method to identify diagnostic horizons that develop in the endopedon. South Kalimantan is one of the areas where ultrabasic rocks are distributed and is an area with a wet tropical climate. The weathering force of the parent material will be faster in the wet tropics. Ultrabasic rocks in each region have different mineral and chemical compositions. Based on the research results, the Oxic horizon in Profile-1 was found at a depth of 29 cm to 76 cm from the ground surface. While in Profile-2 the Oxic horizon was found at a depth of 19 cm to 110 cm from the ground surface. The formation of the oxic horizon is due to the Latosolization process. Such as the long laterization process is supported by environmental conditions, climate, and rainfall making this laterization process will be better.